Job Safety Analysis (JSA) of Work Accidents on Wood Work Machines in the Construction Workshop - Muffi, Khairi; Abdullah, Rijal (CIVED, 2024)
This research was motivated by the occurrence of work accidents that occurred in wood construction workshops and also the magnitude of potential hazards that might cause work accidents. The purpose of this study is first; To reveal how many types of static machines there are in the wood construction workshop. Second; Reveal the forms of accidents that have the potential to occur in woodworking machines. Third; Conduct JSA on the form of potential hazards of work accidents that may occur in the use of wood work machines. This type of research is quantitative descriptive with a survey method using the Guttman scale which produces percentages. This research was conducted on lecturers of wood work practice courses along with technicians of the Wood Construction Workshop of the Department of Civil Engineering FT UNP. The findings of this study are that first; The number of types of static wood work machines used routinely by students / lecturers in wood construction workshops is 6 (six), namely armed-arm circular saws, flattening crabs, thickening crabs, tabled circular saws, chisels, and combination crabs. Second;Forms of work accidents that may occur include the use of machines exceeding normal limits, machine layout, machine maintenance processes, experience of machine use processes, maintenance on machines, the occurrence of short circuit sources on machines, cleanliness of the work environment, and implementation of machine usage procedures. Third; JSA in this study is to control aspects of machine operation including by requiring all students to use complete personal protective equipment, giving obligations to lecturers of courses and practices along with technicians or instructors to strictly supervise the use of machines that have the potential to cause accidents.